Advances in Macromolecules Perspectives and Applications - Russo, Maria Vittoria; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Advances in Macromolecules demonstrates the recent advances in the research and development of macromolecules with particular emphasis on synthetic and naturally occurring polymeric materials. Many examples and figures are provided for the most investigated macromolecules in the fields of basic research and technological applications. The importance of macromolecular nanostructures in the breakthrough of science is extensively addressed from the point of view of synthesis routes, characterization (e.g. XPS and NEXAFS spectroscopy) and outstanding properties (e.g. second order non linear optical (NLO) properties). Fundamental advances in the field of biotechnology and biomedicine that include the involvement of macromolecules are also highlighted due to their future challenges and capacity for the improvement of health and nanotechnology. The reviewed, multidisciplinary topics of the book endeavour to stimulate scientists$1 (Binterest in this fascinating field of materials science. A concise but non-exhaustive overview of both new and classic noteworthy literature is addressed. The introduction to each chapter illustrates the basic concepts which are required for the understanding of the related subjects, with the aid of schemes, formulas and figures. This approach is dedicated to graduate students who are interested in the main issues that are the most exciting and challenging in macromolecular science.s
Nanostructured Macromolecules -- Macromolecular Systems with Second Order Nonlinear Optical Properties -- Macromolecular Systems with Nonlinear Optical Properties: Optical Characterization and Devices -- Functional and Nanostructured Materials Investigated by XPS and NEXAFS Spectroscopies -- Hybrid Systems Biomolecule-Polymeric Nanoparticle: Synthesis, Properties and Biotechnological Applications.
Keywords: Chemistry, Physical organic; Polymers; Biochemistry; Materials; Nanotechnology; Surfaces (Physics).; Materials Science; Materials Science, general; Physical Chemistry; Characterization and Evaluation of Materials; Polymer Sciences; Nanotechnology; Biochemistry, general